Strengthening productive capacity and resilience of smallholder sweet potato producer organizations in Uganda - International Potato Center (2025)
This project report describes a four-year initiative to strengthen the productive capacity, resilience, and market integration of smallholder sweetpotato producer organizations in Eastern Uganda. Led by the Soroti Sweet Potato Producers and Processors Association (SOSPPA) with technical support from the International Potato Center (CIP), the project promotes increased production, processing, and value addition of orange-fleshed sweetpotato (OFSP). Through improved seed systems, climate-smart practices, nutrition education, and organizational capacity building, the initiative aims to increase farm incomes, improve dietary diversity, and enhance food and nutrition security for more than 20,000 beneficiaries.